A novel apatite, Lu5(SiO4)3N:(Ce, Tb), phosphor material: synthesis, structure and applications for NUV-LEDs. Issue 23 (11th May 2016) - Guo, Qingfeng; Wang, Qidi; Jiang, Liwei; Liao, Libing; Liu, Haikun; Mei, Lefu
Abstract : Crystal structure and luminescence properties of novel lutetium containing nitride–apatite Lu5 (SiO4 )3 N:Ce 3+, Tb 3+ . Abstract : The lutetium containing nitride apatite Lu5 (SiO4 )3 N was prepared by a solid state reaction at high temperature for the first time. Rietveld refinement indicated that the Lu5 (SiO4 )3 N compound has a hexagonal space group of P 63 / m with cell parameters a = b = 9.700 Å and c = 7.238 Å. Additionally, the results revealed that there are two distinct lutetium sites in the Lu5 (SiO4 )3 N host lattice, i.e. a Lu(1) site with nine coordination (Wyckoff site 4f) and a Lu(2) site with seven coordination (Wyckoff site 6h). Furthermore, the ratio of the number of Lu atoms in Lu(1) and Lu(2) sites is 3 : 2. The band gap for Lu5 (SiO4 )3 N was determined to be 4.12 eV based on the density functional theory (DFT). In the Ce 3+ doped Lu5 (SiO4 )3 N:0.03Ce 3+ compound, the emission peak centered at 462 nm was observed with the Commission International de I'Eclairage (CIE) coordinates of (0.148, 0.184), indicating blue-emission. Remarkably, in Ce 3+ and Tb 3+ co-doped Lu4.97− y (SiO4 )3 N:0.03Ce 3+, y Tb 3+ compounds, the color-tunability was observed with increasing Tb 3+ co-doping rate on moving from blue at Tb 3+ = 0.00 to green at Tb = 0.09, due to the energy transfer from Ce 3+ to Tb 3+ ions being matched well with the decay curve results. Under the excitation at 359 nm, the absolute quantum efficiency (QE) for Lu5 (SiO4 )3 N:0.03Ce 3+ was determined to be 42.13%. This phosphor material could be a platform for modeling a new phosphor and application in the solid-state lighting field.